389 Neutrophils: Novel Contributors to Estrogen-Dependent Intracranial Aneurysm Rupture Via Neutrophil Extracellular Trap Formation. (April 2023) - Patel, Devan; Dodd, William S.; Lucke-Wold, Brandon; Hosaka, Koji; Hoh, Brian Lim
Abstract : INTRODUCTION: Intracranial aneurysms (IAs) are more prevalent in women than men and aneurysmal subarachnoid hemorrhage disproportionately affects postmenopausal women. These sex differences suggest estrogen protects against IA progression that can lead to rupture, but the underlying mechanisms are not fully understood. Although studies have demonstrated estrogen regulates inflammatory processes that contribute to IA pathogenesis, the role of neutrophils remains to be characterized. METHODS: We compared neutrophil infiltration in C57BL/6 mice that develop IAs to those with a normal circle of Willis. Next, we investigated the role of neutrophils in female estrogen-deficient mice, female estrogen-intact mice, and male mice using a neutrophil depletion antibody. Finally, we studied the role of neutrophil extracellular trap formation (NETosis) as an underlying mechanism of aneurysm progression. RESULTS: Mice that developed aneurysms had increased neutrophil infiltration compared to those with a normal circle of Willis. In female estrogen-deficient mice, both neutrophil depletion and NETosis inhibition decreased aneurysm rupture, but not formation, and had no effect on symptom-free survival. In female estrogen-intact mice, neither neutrophil depletion nor NETosis inhibition affected IA formation, rupture, or symptom-free survival. In male mice, neutrophil depletion decreased IA formation but did not affect rupture or symptom-free survival. NETosis inhibition in male mice did not affect IA formation, rupture, or symptom-free survival. CONCLUSIONS: Neutrophils contribute to aneurysm rupture in the setting of estrogen deficiency. NETosis appears to be an underlying mechanism for neutrophil-mediated IA rupture in estrogen deficiency. In males, neutrophils contribute to IA formation, but not rupture. Targeting NETosis may lead to the development of novel therapeutics to protect against IA progression, particularly IA rupture in post-menopausal women.